(untitled) (Annals of Medical Research, 2021)
Aim: Scapular and core muscle endurance is known to reduce risk of injury and improve performance. But, there was no study investigating relationship between scapular and core muscle endurance in athletes. To identify relationship between scapular and core muscle endurance in professional athletes. Material and Methods: Fifty-two professional athletes (basketball, football and handball players) (age:19.88±5.98, BMI:21.65±2.82) were included in study. Scapular muscle endurance was assessed with scapular endurance test. Core muscle endurance was evaluated using McGill core endurance tests (trunk flexion, Sorensan test, and the side bridge) and prone bridge test. Results: Spearman correlation analysis results showed that a positive moderate correlation was found between scapular endurance and prone bridge test (r: 0.524, p: 0.000). Scapular endurance test was shown to have positive correlations with Sorensen test (r: 0.292, p: 0.039).Conclusion: Scapular and core muscle endurance is very important in performance and identifying risk of injury. As a result of this study, it can be seen that in athletes, scapular muscle endurance increases as core muscle endurance increases. This suggests that development of scapular and core muscle endurance in athletes is necessary for performance and for prevention of injuries. There is need for additional studies to investigate effect of scapular and core muscle endurance on performance and injury risk in athletes.Keywords: Scapular endurance; core muscle endurance; athletes.